Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.063
|View full text |Cite
|
Sign up to set email alerts
|

Situational Awareness and Systems for Driver-Assistance

Abstract: Low level of driver's situation awareness (SA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In relation to driving in a UFTR, the study [8] discovered the drivers' SA when driving at a UFTR by testing the lane changing performance at straight and curved roads in addition to roundabouts and intersections. The findings of [8] showed that international drivers are likely to have low SA when driving at roundabouts and intersections. Accordingly, the current study focuses on driving at roundabouts and intersections in a UFTR.…”
Section: A Situation Awareness In Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to driving in a UFTR, the study [8] discovered the drivers' SA when driving at a UFTR by testing the lane changing performance at straight and curved roads in addition to roundabouts and intersections. The findings of [8] showed that international drivers are likely to have low SA when driving at roundabouts and intersections. Accordingly, the current study focuses on driving at roundabouts and intersections in a UFTR.…”
Section: A Situation Awareness In Drivingmentioning
confidence: 99%
“…In relation to driving in a UFTR, the study [8] extracted the required information to drive safe at roundabouts and intersections. The information included upcoming area of the road to inform the driver about the upcoming roundabout and intersection, travelling path to inform the driver about the correct travelling lane when approaching, entering and exiting a roundabout/intersection, direction indicator to remind the driver of the correct position of direction indicator stalk, and speed to inform the driver about the speed limit of the travelling road.…”
Section: Augmented Feedback In Drivingmentioning
confidence: 99%
“…SA in driving is formally defined as the recognition of the component of the traffic system within the limits of time and space to fully understand the meaning of those components and predict the correct decision in the future according to that understanding [4]. It can be measured indirectly using performance-based assessment [5][6][7] and subjectively using the Participant Situation Awareness Questionnaire (PSAQ) [8][9][10]. The drivers also need to adapt the driving skills that they already have when driving in their familiar environment to match the requirements of the UFTR and thus to safely reach the target destination.…”
Section: Introductionmentioning
confidence: 99%
“…That produces adaptive ADAS functionalities and warnings or information in accordance with the driver's skills [17] and workload [18] or other factors. A few studies have investigated the situation awareness in unfamiliar traffic regulations, such as [7,19], which might lead to covering more drivers' needs in such driving conditions and thus to designing better ADASs. However, there is still a need for further investigation to clearly describe the influence of degree of handedness on SA when driving under unfamiliar traffic regulations in regard to developing an efficient, adaptive ADAS.…”
Section: Introductionmentioning
confidence: 99%